THE EFFECT OF CONTEXTUAL TEACHING AND LEARNING IN WRITING RECOUNT TEXT - Afifah Anggraeni Sekar; Amir Hamzah (English Education and Applied Linguistics Journal (EEAL Journal), 2018)
This research entitled "The Effect of Contextual Teaching and Learning method in writing recount text". This aim of this research is to find out the significant effect of Contextual Teaching and Learning method that used in writing recount text. In this research, the researcher took one Junior High School in Wanaraja academic year 2016/2017. This participant of this research were conducted to 37 students in the 2nd years of Junior High School 1 Wanaraja in 27th July 2016. The researcher used Quantitative method and Pre-experimental design to find out the effect of CTL method. Writing test used in this research were collected Pre-test, Post-test, and treatment. Moreover, this research will use text in the This research also will use pre- experimental research and will focuses on the second grade at one state of Junior high school in Garut . In addition, writing test, pre-test, and post-test will be used to collect the data. Quantitative method will be used to analysethe data to compare the score of both groups in pre-test and post-test.